Analisis Inflation Targeting di Indonesia - Purnomo, Sodik Dwi; Zumaeroh, Zumaeroh (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Inflation targeting is a policy strategy in which inflation is set as the primary objective of monetary policy implementation. Indonesia began adopting this policy framework in 2005. Various economic factors can influence the success of achieving inflation in line with the targets set by the government. Coordination among economic institutions, particularly in the monetary and fiscal sectors, plays a significant role in supporting the achievement of these inflation targets. This study aims to analyze the influence of monetary variables namely the BI-7 Day Reverse Repo Rate, previous period inflation, and the exchange rate as well as fiscal variables, including economic growth, population size, and government expenditure, on the achievement of inflation targets in Indonesia from 2005 to 2021. The method used in this research is multiple linear regression analysis. The results show that monetary and fiscal variables such as the BI-7 Day Reverse Repo Rate, previous period inflation, and population size have a negative effect on inflation targeting. In contrast, the exchange rate and government expenditure positively influence inflation targeting. However, economic growth in Indonesia during the 2005–2021 period does not have a significant effect on inflation targeting.